2017
DOI: 10.18203/2394-6040.ijcmph20174243
|View full text |Cite
|
Sign up to set email alerts
|

A study on assessment of knowledge towards family planning practices among the couples of reproductive age group in the field practice area of Prathima institute of medical sciences, Karimnagar

Abstract: Background: Population explosion is a major problem in developing country like India. Contraception is important for the health of the nation. Hence the present study aimed at elucidating knowledge of the couples towards contraception. Methods: A cross - sectional study was conducted during February 2013-January 2014 among the couples residing in the field practice study areas. A semi-structured questionnaire consisting of socio-demographic characteristics, knowledge towards various methods of family planning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…The mean knowledge score of males was 7.76+2.33 with obained range of 2-13 and the mean knowledge score with standard deviation of females was also 7.76+2.33; median was 8 with obtained range of 2-13 whereas the mean attitude score of males was 96.26+12.71; median was 96.50 with obtained range of 73-125 and the mean attitude score of females was 97.6+ 12.49; median was 97.50 with obtained range of 76-125. These findings were contradictory to the results of the study by Gayathry, D., 2014 who observed that females had higher scores as compared to males which was not significant between the overall knowledge score (18.67+7.798 vs. 18.41+7.177) 6 .…”
Section: Discussioncontrasting
confidence: 94%
“…The mean knowledge score of males was 7.76+2.33 with obained range of 2-13 and the mean knowledge score with standard deviation of females was also 7.76+2.33; median was 8 with obtained range of 2-13 whereas the mean attitude score of males was 96.26+12.71; median was 96.50 with obtained range of 73-125 and the mean attitude score of females was 97.6+ 12.49; median was 97.50 with obtained range of 76-125. These findings were contradictory to the results of the study by Gayathry, D., 2014 who observed that females had higher scores as compared to males which was not significant between the overall knowledge score (18.67+7.798 vs. 18.41+7.177) 6 .…”
Section: Discussioncontrasting
confidence: 94%
“…In other studies done on the knowledge, attitude and practice of contraception majority of the participants were in the same age group. 8,9 An extensive review of literature did not reveal many studies done among pregnant women in India. Most of the studies have been done among non pregnant women in reproductive age group.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the other studies showed a greater awareness regarding oral contraceptive pills when compared to Intrauterine devices. 8,9,13 A study done in Coimbatore on pregnant mothers found an 83% awareness of oral contraceptive pills and only 10% awareness of IUCD. 14 All the studies done so far reveal a very low knowledge regarding Injectable contraceptives.…”
Section: Resultsmentioning
confidence: 99%
“…6 Further, the levels of unwanted pregnancy have been quite high in India among married young women. 7 Present study was aimed at focusing contraceptive practices of females in early reproductive age and females who are in late reproductive age group for better understanding of unmet need of contraception in both these groups. Females in early reproductive age are most of the time unaware about availability of various contraceptive methods and have unplanned pregnancies.…”
Section: Introductionmentioning
confidence: 99%